2018
DOI: 10.1371/journal.pone.0201521
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in the categorical processing of positive and negative facial expressions

Abstract: Categorical biases in the processing of emotional facial expression have been the subject of much debate in the literature. Opposing views on this topic claim either that positive or negative facial expressions enjoy improved processing in the human brain. The developmental changes in the processing advantages of positive and negative facial expressions are also disputed, with studies using varying paradigms showing seemingly contradictory results. Therefore, to further investigate the development of categoric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…The overview of these studies therefore offers some hints that age might in fact play a role in the appearance of positivity and negativity biases. This finding is also supported by the results of a positive/negative face-categorization experiment (Vesker et al, 2018a), where the authors found an initial positivity bias with younger children, but which gradually disappeared, and in some cases even reversed into a negativity bias with increasing age.…”
Section: Review 2: Studies On Valence Effects In Face Processingsupporting
confidence: 69%
See 3 more Smart Citations
“…The overview of these studies therefore offers some hints that age might in fact play a role in the appearance of positivity and negativity biases. This finding is also supported by the results of a positive/negative face-categorization experiment (Vesker et al, 2018a), where the authors found an initial positivity bias with younger children, but which gradually disappeared, and in some cases even reversed into a negativity bias with increasing age.…”
Section: Review 2: Studies On Valence Effects In Face Processingsupporting
confidence: 69%
“…After checking ~400 titles and abstracts, four studies could be identified that report valence effects in both modalities along the criteria mentioned above (see Table 1). In these studies, valence effects in adult populations either did not appear at all (Rellecke et al, 2011, accuracy outcomes in Bahn et al, 2017; Vesker et al, 2018a), converged for words and faces (judgement task in Feyereisen et al, 1986), or a valence effect was found in one modality, while no effect of valence emerged in the other modality (categorization task in Feyereisen et al, 1986; Schacht and Sommer, 2009, reaction time outcomes in Bahn et al, 2017; Vesker et al, 2018a).…”
Section: Review 3: Studies On Valence Effects With Words and Faces Asmentioning
confidence: 84%
See 2 more Smart Citations
“…The results of our experiments reproduced the early positivity bias for words and faces reported by earlier studies using the same valence-based emotional categorization task (Bahn et al, 2017b;Vesker et al, 2018a), wherein younger children tended to show faster and more accurate responses to positive stimuli versus negative stimuli, with this positive/negative disparity diminishing with increasing age. However, we did not detect any significant effects of embodiment on the categorization of either faces (Experiment 1a) or words (Experiment 2) using the manipulation of facial musculature to either facilitate or inhibit smiling based on the original "pen-in-the-mouth" approach described by Strack et al (1988).…”
Section: Discussionsupporting
confidence: 87%